Q. 154.5( 8 Votes )

# Find <span lang="

Answer :

Let, f (x) = *x*^{3}+3*x*^{2}-2α*x*+β be the given polynomial,

From factor theorem,

If (x + 1) and (x + 2) are factors of f (x) then f (-1) = 0 and f (-2) = 0

f (-1) = 0

(-1)^{3} + 3 (-1)^{2} – 2 α (-1) + β = 0

-1 + 3 + 2 α + β = 0

2 α + β + 2 = 0 (i)

Similarly,

f (-2) = 0

(-2)^{3} + 3 (-2)^{2} – 2 α (-2) + β = 0

-8 + 12 + 4 α + β = 0

4 α + β + 4 = 0 (ii)

Subtract (i) from (ii), we get

4 α + β + 4 – (2 α + β + 2) = 0 – 0

4 α + β + 4 - 2 α - β - 2 = 0

2 α + 2 = 0

α = -1

Put α = -1 in (i), we get

2 (-1) + β + 2 = 0

β = 0

Hence, α = -1 and β = 0.

Rate this question :

Factorize:

</pRS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:

</pRS Aggarwal & V Aggarwal - Mathematics

Factorize:

</pRS Aggarwal & V Aggarwal - Mathematics

Factorize:

</pRS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:

</pRS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar